Anxiety disorders and intimate partner violence: can the association be explained by coexisting conditions or borderline personality traits?. Issue 5 (3rd September 2017) - Davoren, Mary; Kallis, Constantinos; González, Rafael A.; Freestone, Mark; Coid, Jeremy W.
Abstract: Intimate partner violence (IPV) is a serious, preventable public health problem. IPV perpetration is strongly associated with Anxiety disorders at the population level. We investigated whether the association could be explained by coexisting psychiatric conditions or Borderline personality traits, using a combined data-set of two National Household Surveys ( n  = 15, 973). Results showed women were more likely to report perpetrating IPV than men. Anxiety disorders were associated with IPV. When coexisting psychiatric conditions together with a categorical diagnosis of Borderline Personality Disorder (BPD) were investigated as explanatory variables, 19.2% of the association between Anxiety disorders and IPV was explained. Using individual Borderline traits in place of a categorical diagnosis of BPD, 58.3% of the association was explained. In conclusion, the association between Anxiety disorders and IPV was partly, but not fully, explained by coexisting psychiatric conditions and individual Borderline traits. Perpetrators of IPV should be screened for Anxiety disorders and among those with Anxiety disorders, Borderline traits are important.